2013
DOI: 10.1097/qai.0b013e31829260d6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Low-Dose Ritonavir With and Without Darunavir on the Pharmacokinetics and Pharmacodynamics of Inhaled Beclomethasone

Abstract: Objective To identify an alternative inhaled corticosteroid to fluticasone propionate that can be safely coadministered with HIV protease inhibitors (PIs), we assessed the safety and pharmacokinetics of beclomethasone dipropionate (BDP) and its active metabolite, 17-monopropionate (17-BMP), in combination with ritonavir (RTV) and darunavir/ritonavir (DRV/r). Design Open label, prospective, randomized pharmacokinetic and pharmacodynamic study in healthy volunteers. Methods Thirty healthy volunteers received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…6267 Most case reports describe interactions between fluticasone and protease inhibitors, but the clinician should be aware that other inhaled corticosteroids including budesonide and, to a lesser extent, beclomethasone, can lead to hypercortisolism symptoms if they are given concomitantly with protease inhibitors. 6870 The 2013 update of the antiretroviral treatment guidelines 71 advised clinicians to avoid co-administration of ritonavir-based ART with inhaled budesonide or fluticasone, unless the benefits clearly outweighed the risks; however, inhaled beclomethasone was not included in this advice. The adverse side-effects of inhaled budesonide or fluticasone combined with ART seem reversible with cessation of the inhaled corticosteroid.…”
Section: Pharmacotherapy Recommendations For Hiv-infected Patients Wimentioning
confidence: 99%
“…6267 Most case reports describe interactions between fluticasone and protease inhibitors, but the clinician should be aware that other inhaled corticosteroids including budesonide and, to a lesser extent, beclomethasone, can lead to hypercortisolism symptoms if they are given concomitantly with protease inhibitors. 6870 The 2013 update of the antiretroviral treatment guidelines 71 advised clinicians to avoid co-administration of ritonavir-based ART with inhaled budesonide or fluticasone, unless the benefits clearly outweighed the risks; however, inhaled beclomethasone was not included in this advice. The adverse side-effects of inhaled budesonide or fluticasone combined with ART seem reversible with cessation of the inhaled corticosteroid.…”
Section: Pharmacotherapy Recommendations For Hiv-infected Patients Wimentioning
confidence: 99%
“…There is some evidence that inhaled or intranasal beclometasone is a relatively safe option in patients receiving protease inhibitors or cobicistat. 8 In this case, it was not necessary to alter the antiretroviral therapy to prevent the interaction. However, when longer acting steroids are used, such as intra-articular or epidural triamcinolone injections, 6 9 it may been necessary to remove the ongoing interaction by switching from ritonavir to a different antiretroviral therapy regimen.…”
Section: Discussionmentioning
confidence: 97%
“…One study of healthy volunteers showed that beclomethasone in combination with ritonavir does not lead to adrenal suppression tested by an ACTH-stimulation test [7]. This study and pharmacokinetic evidence has resulted in the general advice to change the inhalation corticosteroid fluticasone to beclomethasone if a patient also uses a CYP3A4 inhibitor [3,4] This advice was already actively implemented in the involved hospitals.…”
Section: Discussionmentioning
confidence: 99%